172k views
15 votes
Please help me! 20 points!

Enter your answer and show all the steps that you use to solve this problem in the space provided.

simplify
(in attachment)

Please help me! 20 points! Enter your answer and show all the steps that you use to-example-1
User Nihal
by
4.6k points

2 Answers

8 votes

Explanation:

When we multiplying, we find the sum of the exponents so


3 {}^{ (1)/(2) } * 3 {}^{ (1)/(2) } \\ {3}^{ (1)/(2) + (1)/(2) } \\ = {3}^{ (2)/(2) } \\ = 3

User SelvaMariappan
by
5.1k points
13 votes

Answer:

12 1/4 or (Decimal: 12.25)

Explanation:

(3 1/2) (3 1/2)

= 7/2 (3 1/2)

= 7/2 (7/2)

= 49/4

= 12 1/4

I hope I helped you!!

User MatlabNewb
by
5.0k points